Psychometric Properties and Factor Structure of the Chinese Version of the Hospital Anxiety and Depression Scale in People Living With HIV - Yang, Zhiyuan; Huang, Xiaojie; Liu, Xinchao; Hou, Jianhua; Wu, Wenfang; Song, Aixin; Meyers, Kathrine; Zhang, Tong; Chen, Hui; Wu, Hao (Frontiers in Psychiatry, 2019)
The population of people living with HIV (PLWH) is growing in number and usually has mental health problems that impact their quality of life. Therefore, valid instruments and screening methods for psychological disorders are of great significance. The Hospital Anxiety and Depression Scale (HADS) has good psychometric properties but shows ambiguous results in factor structure. This study aims to evaluate psychometric properties in terms of internal reliability and structure validity of the Chinese version of HADS (C-HADS) in a large sample of PLWH in China. The C-HADS was administered to 4102 HIV-infected adults at an HIV clinic in China. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed to examine the factor structure. Measurement invariance was assessed across gender and course of infection. Internal reliability was also assessed. A bifactor model with anomalous loadings of item 7, 8 and 10 fits the data best and holds measurement invariance across gender and course of infection. Internal reliability was good with all Cronbach’s alphas > 0.70 and Spearman’s between 0.30 and 0.70. The C-HADS has good psychometric properties in terms of internal reliability and structure validity of a bifactor model. The C-HADS is recommended to be used as a total scale that measures general psychological distress instead of anxiety and depression separately when applied to PLWH. Further studies are needed to evaluate criterion validity and cut-off score as well as the effect of wording and scoring of the HADS.